"Many a Wish Has Turned to Dust" the royal Aq Quyunlu Khamsa of Nizami - al Nashar, Dalia R. (AUC Knowledge Fountain, 2018)
…[A]nd our reason for relating this narrative is as follows. Before now the late padishah Babur Mirza intended to complete this eloquent book, which is attributed to the “Treasure of Ganja,” scatterer of riches from the treasure house of the Khamsa, Sultan of Poets Nizami, and commanded Azhar, who was one of the rarities of his age in calligraphy, to copy it. Not yet had [Babur Mirza] plucked the rose of desire from the garden of completion when the barren wind of autumn of fate left not a leaf on the tree of his life. Thereafter, Pir-Budaq Mirza was seized by the same desire [to have the work completed]. Still unsuccessful, he withdrew the foot of his life into the skirt of death, and he too, not having quaffed of this goblet, carried the baggage of existence to the waystation of nothingness. Thereafter, Sultan Khalil, son of Sultan Hasan, desired to have it completed. He had it copied by Anisi, who had snatched the ball of precedence from his peers; and for the painting he commissioned Master Shaykhi and Master Darwish Muhammad, who were second only to Mani. Scarcely had one of the “Five Treasures” been completed when the patrol of misfortune shackled the hand of his prosperity, and he too stopped in the lane of annihilation, turning over his workshop to his brother, Ya‘qūb. He too strove to have it finished and exerted much effort, but suddenly the victor death seized him by the collar, and he too stepped into the wildness of nonexistence. In accordance with the saying, “Many a wish has turned to dust,” none of them was able to achieve this goal or drink in fulfillment from the goblet of competition. Although all wished it, it was but in their keeping during their days. [however], in the felicitous time if the Leader of Mankind, His Exalted Highness, Shadow of God, Refuge of the World, who was prefigured in the Qurʾānic verse, “and mention in the book of Ishmael,” … bestower of crowns and thrones … in accordance with God’s word, “the earth shall be inherited by my pious servants,” it was completed as wished through the care and concern if His August Majesty. By those rhetorical words, the convoluted history of an illustrated copy of Nizami’s Khamsa (Quintet) was documented. This Khamsa, known today as the royal Aq Quyunlu Khamsa of Nizami, took almost half a century to be completed, during which it exchanged hands between a line of patrons, Timurid: Abu’l-Qasim Babur (d. 1457), Qara Quyunlu (Black Sheep) Turkman: Pir Budaq (d. 1466), Aq Quyunlu (White Sheep) Turkman: both Khalil (d. 1478) and his brother Ya‘qub (d. 1490) and finally Safavid: Shah Isma‘il (d. 1524). This Khamsa’s history can be seen through the change in its nasta‘liq calligraphy, from Azhar to ‘Abd al-Rahim al-Khwarazmi and finally to an unknown calligrapher who wrote the postscript, and in the changes in the style of its twenty-two illustrations. One way or another, this Khamsa reached the Ottoman treasury, and today it’s part of the Topkapi Sarayi Library collection under the archive number Hazine 762. According to the manuscript’s two colophons and postscript, what is represented today in the manuscript is the work of calligraphers and artists who worked under one or both patrons Ya‘qub and Shah Isma‘il. The common ground between the two periods is the location where the manuscript was begun and completed, which is the royal workshop in Tabriz, Dar al-Saltana. The limited number of surviving royal manuscripts known to scholars produced during this troubled period, especially those stating Tabriz as their location of production, makes this Khamsa a milestone in the history of Persian painting. Although recent studies were dedicated to the production of manuscripts, either illustrated or not, during the Turkman and the early Safavid period, none was confined to the production of the royal workshop in Tabriz. The elements of the manuscript, especially its illustrations, were used by earlier scholars either as a case study for the influences of the Herat and Shiraz Timurid school on Turkman illustrations, or how the Safavid school was influenced by the Turkman style, but never as real evidence of how artists were given the freedom to experiment with new features to reach a new style. Based on the above, there is still progress to be made regarding the understanding of the expermintation that took place in the Tabriz workshop in an attempt to assemble a distinctive pictorial style that would distinguish Aq Quyunlu work from Safavid. Thus, with the aid of several recently released studies, this thesis will attempt to show how artists in the Tabriz workshop, under both the Turkmans and the Safavids, studied earlier and contemporary Persian paintings and forged a new pictorial style that would distinguish their dynasty, either the Turkman or the Safavid.